P-86 Research priorities for children with life-limiting conditions: who has already prioritised what?. Issue Volume 7:Issue (2017)Supplement 2 (1st November 2017) - Booth, Alison; Maddison, Jane; Beresford, Bryony; Fraser, Lorna
Abstract : Background: A new multi-disciplinary centre committed to leading research on the management, care and support of children with life-limiting conditions and their families was recently established. To inform decisions on the focus of the work of the Centre, a Research Prioritisation Exercise (RPE) is being undertaken. In designing our RPE we took into account our broad scope, awareness of existing RPEs relevant to children with life-limiting conditions (LLC) and the need to maximise resource use. The first part of this project has therefore been to undertake a systematic scoping review of existing RPEs. Aims: Our scoping review aims to map existing RPEs relevant to children, young people with life-limiting conditions and their families and carers. The findings will be used to develop a framework of existing priorities, and to inform the design and format of our own research consultation exercise. Methods: We have used systematic review methods to identify and select relevant published RPEs, and identify quality markers for RPE methods. The synthesis will provide an overview of the conditions and/or settings where priorities have been set and present the areas that are most frequently identified as priorities for future research. Results: We have identified 26 RPEs for inclusion, most use the Delphi technique. The majority were about those requiring paediatric oncology or palliative services. Most were undertaken by health professionals, with only a few including patients and/or parents in the consensus exercise. Synthesis of the priorities identified is underway and the results will be included in the presentation. Conclusions: A number of robust RPEs examining what is most important for health professionals delivering care to children with LLCs exist. However, more could be done to ensure that the values and experiences of children and young people, their families and other carers are accounted for.